Kemampuan membaca pemahaman ditinjau dari minat membaca dan penguasaan diksi peserta didik kelas IV sekolah dasar - Safitri, Hanifah Nur Ekayati; Slamet, St Y; Budiharto, Tri (Didaktika Dwija Indria, 2021)
This purpose of this research was 1) know wheter there was a correlattion between the reading interest and the competency of reading comprehension; 2) knowing whether there was a correlattion between the diction mastery and the competency of reading comprehension; 3) knowing whether there was a correlation between both the reading interest and the diction mastery toghether with the competency of reading comprehension.The research was a quantitative survey correlational study. The population of this research was all the students of government elementary school at grade 4TH in kartasura for about 39 schools. The sample of this research was taken with simple random sampling technique.  Five elementary schools was used as the sample by taking the whole students of grade 4 of each government elementary school with the total amount of the students is 110 students.The data was collected through the test instrument in the form of objective choice for the variable of the competency of reading comprehension and also the diction mastery. It was also collected through the questionnaire for the variable of reading interest given to the students. Based on the data analysis, it can be concluded that there was a significant correlation between the reading interest and the competency of reading comprehension ry1 (0.60034), the coefficient of the correlation was tested with the t test, the result tcount (7.8011)> ttable (1.9822) showing a significant correlation between the diction mastery and the competency of reading comprehension ry2 (0.794),, the coefficient of the correlation was tested with the t test, the result tcount (13.5745)> ttable (1.982)showing a significant correlation  between both  the reading interest and the diction mastery with the competency of reading comprehension ry12 for about 0,815. The coefficient of significance with the F test obtained Fcount = 106.00131 real level á = 0.05, with df =107 obtained Ftable = 3.081 then Fcount > Ftable.